Penggunaan Teknik Tongue Twister dalam Pembelajaran Pronunciation Bahasa Inggris: Studi Kasus pada Siswa Kelas IX di SMP Negeri 3 Denpasar - Ni Komang Dwiki Guswani; Ni Wayan Satri Adnyani; Ni Ketut Riska Dewi Prawita (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2026)
This study investigated the implementation of the tongue twister technique in teaching English pronunciation and explored students’ perceptions at SMP Negeri 3 Denpasar. A case study design supported by questionnaire data was employed involving 81 ninth-grade students. Data were collected through classroom observation, teacher and student interviews, and questionnaires. The findings showed that the technique was implemented through modelling, repetition, and individual practice, creating an interactive learning environment. Most students responded positively, reporting improved pronunciation, speaking fluency, and confidence. Despite challenges in pronouncing similar sounds and memorizing sentences, the tongue twister technique effectively enhanced students’ pronunciation learning experien